Biodegradation of Chlorpyrifos by Microbes: A Review - Rubiyatno; Maulana, Aulia; Tongco, Jovale Vincent; Yulisa, Arma; Park , Sang Hyeok; Jannat, Md Abu Hanifa; Permana, Rega; Thakali, Ocean; Lie, Michael; Fahssi, Aouatif; Aziez, Ouahiba; Bastidas, Camilo (Tropical Aquatic and Soil Pollution, 2024)
Chlorpyrifos (CP) is a widely used organophosphate pesticide known for its recalcitrant nature, raising concerns about potential ecological and health impacts due to its toxicity. Many plants and animals are contaminated with this pesticide. Microbial biodegradation offers an environmentally friendly and effective method to remove CP from the environment and mitigate its impacts, especially given its low cost, particularly when bioremediation is conducted on-site. Different types of microbial species have been found to function under various environmental conditions, with some, like Pseudomonas nitroreducens PS-2 and Pseudomonas aeruginosa (NCIM 2074), showing promising results with degradation rates of up to 100%. However, challenges exist, such as partial degradation caused by the presence of metabolites, and the recalcitrant nature of CP, which can impede microbes' ability to effectively degrade its hydrocarbon ring. Overall, a combination of approaches, such as microbial and algal methods, or the discovery of new microbial strains, can help overcome these challenges and further enhance the long-term viability of this technique.